Ästhetik im Vormärz. Jahrbuch Forum Vormärz Forschung 2020

Die Landstraße jenseits der Bedeutung. Peter Handkes spätes Drama Die Unschuldigen, ich und die Unbekannte am Rand der Landstraße - Famula, Marta (Literatur und Kultur zwischen West und Ost. Imagination, Kommunikation und Wahrnehmung in regionalen Kulturräumen. Festschrift für Paul Martin Langner zum 65. Geburtstag)

Von der auf den Kopf gestellten Schönheit oder die Verneinung der Negation im Hässlichen. Zur dialektischen Funktion des Erhabenen und des Hässlichen bei Christian Hermann Weiße - Famula, Marta (Ästhetik im Vormärz. Jahrbuch Forum Vormärz Forschung)

Vom Entschluss, die Welt zu bestehen. Dürrenmatts Ethik des ‚à la bande‘ - Famula, Marta (Kosmos Dürrenmatt. Eine Annäherung an den Denker, Dichter und Maler. Berner Zeitschrift für Geschichte, H. 3. Sonderdruck Spiezer Tagung, in: Annelise Hüssy, Stefanie Leuenberger (Hgg.))

Ästhetik im Vormärz – Zur Einführung - Famula, Marta; Otto Eke, Norbert (Ästhetik im Vormärz. Jahrbuch Forum Vormärz Forschung 2020)

Lukas Bärfuss: Malinois. Erzählungen. Wallstein: Göttingen 2019 - Famula, Marta (Jahrbuch für internationale Germanistik, Jahrgang LIII – Heft 1 (2021))

Das Unveränderliche und die Wiederholung. Die Rolle der Kontingenz in Max Frischs letztem Drama Triptychon - Famula, Marta (Wiederholung im Theater. Zur deutschsprachigen Gegenwartsdramatik und ihrer Inszenierung, (= Gesellschaftskritische Literatur – Texte Autoren – Debatten 9))

Drama zwischen Text und Bühne (Schriftenreihe seit 2021)

Orthografieunterricht heute. Theorie – Empirie – Didaktik

Das ,rechte Schreiben‘ lernen. Von der Buchstabiermethode zur sprachsystematischen Vermittlung - Köller, Katharina; Tophinke, Doris (Der Deutschunterricht)

Zur Wirkung der universitären DaZ-Weiterbildungen an den Standorten Duisburg-Essen, Münster und Paderborn. Auswertung von schriftlichen Reflexionen teilnehmender Lehrkräfte - Asmacher, Judith; Borowoski, Damaris; Böttger, Lydia; Islinger, Günter; Robers, Christin (Universitäre Weiterbildungen im Handlungsfeld von Deutsch als Zweitsprache)

Brand names as multimodal constructions. On the role of typography as an additional indicator of onymisation. - Dübbert, Alexander (Linguistics Vanguard)
Brand names are a common part of the everyday consumer environment, and can be found on countless visual surfaces such as food packaging. A key characteristic of brand names is their fixed design. Many brand names owe their linguistic form to units that originally did not constitute proper names. They developed into brand names through complex sub-processes of what is commonly referred to as onymisation. These processes include semantic, morphological and phonological/graphemic changes. The aim of this paper is to explore how the specific typographic design of a brand name can be an additional indicator in its process of onymisation. After clarifying the concepts of onymisation and typographic design, an extended multimodal construction model is presented. The basis of the paper is an analysis of a corpus of image data comprising more than 600 photographs of food packaging. In order to get a first impression of how the multimodal constructions of brand names could look, an omission test following a suggestion by Ziem (2017) is applied to the data.

Angstkonstruktionen zwischen „sinnvoller Vorsicht und sinnloser Panik“ - Georgi, Christopher (Angstkonstruktionen)

Digitally Assessing Text Comprehension in Grades 3-4: Test Development and Validation - Seifert, Susanne; Paleczek, Lisa (Electronic Journal of e-Learning)
A prerequisite for child reading support at school is adequate assessment. Embedding (repeated) assessment into daily teaching routine is often challenging for teachers in terms of time and organization. The use of digital tools can help teachers in the assessment process (in preparation, evaluation, documentation, etc.). A digital assessment tool (Graz Reading Comprehension test: GraLeV), focusing on assessing reading comprehension skills in Grades 3 and 4 is currently being developed in Austria. This reading assessment covers reading comprehension at the word, sentence, and text level. Text level is assessed via two subtests (Subtest I: presentation of nonsense-stories and corresponding questions, and Subtest II: maze selection). The other levels consist of one subtest each. This paper focusses on the subtests at text level. More specifically, the paper reports the results of two studies. Study 1 describes the development phases and the first piloting of these two subtests (data collection: 10/2019-12/2019). Testing 273 students with preliminary versions of the subtests (Subtest I: 30 items, Subtest II: 60 items) produced information on (a) item difficulty, (b) item discriminatory power, and (c) time limits for future speed testing. Items not meeting the required quality criteria were excluded. The final version of Subtest I consists of 16 questions referring to eight different, short, nonsense-texts. Its testing time (without instructions) is three minutes. The final version of the Subtest II consists of 2 texts each with 15 maze selections (30 items) and testing time is 100 seconds. The internal consistency is found to be good for Subtest I (α=.87) and Subtest II (α=.78 to .80). Study 2 reports on testing for validity and retest-reliability (data collection: 09/2020-11/2020). Student scores in another reading comprehension test, together with teacher assessments of reading comprehension, were used to assess congruent validity. Divergent validity was assessed using teacher assessments of mathematical and socio-emotional skills. As expected, the correlations with the congruent measures were higher than those with the divergent measures. A subsample was tested twice with the GraLeV. Retest-reliability was acceptable for Subtest II. However, the scores obtained at time 2 were higher compared to those at time 1 in both subtests. This is probably the result of increased student familiarity with the digital device and the digital test environment at time 2. The results are discussed in the light of teachers’ needs for standardized digital assessments in order to facilitate the tailoring of student reading support.
Keywords: Computer Science Applications; Education

Is Reading Comprehension Taken for Granted? An Analysis of Austrian Textbooks in Fourth and Sixth Grade - Seifert, Susanne (Technology, Knowledge and Learning)
Abstract The range of teaching materials now available is becoming increasingly diverse. Despite this, however, the use and influence of textbooks in teaching still remains very high. When instructing reading comprehension, teachers often use textbooks as the basis for teaching in language lessons. Establishing a good match between textbooks and the skills to be acquired is therefore essential. In this paper, I investigate whether textbooks used in Austrian schools can adequately support the teaching of reading comprehension skills. Since reading comprehension is the basis for acquiring knowledge in all subjects, science textbooks are examined in addition to (German) language lesson textbooks. Thus, the content pages of four language textbooks and four science textbooks for fourth and sixth grade were analysed in terms of five different categories, i.e. general structural setup, learning goals, text types, text structures, and activities. The results reveal clear variations with respect to learning goals in language textbooks. For example, the extent to which reading comprehension is addressed ranges from 13.64 to 69.70%, depending on the book used. Although not addressed as a learning goal in the science textbooks, reading comprehension is often presupposed, especially in sixth grade. While the instruction of reading comprehension ought to entail coverage of reading strategies, this is often neglected, or only dealt with indirectly. Given the diversity of textbooks analysed, it seems all the more important to stress that teachers should: 1) clarify the goals and teaching strategies of a book before using it, 2) become aware of strategies that support the development of students' reading comprehension, and 3) use textbooks as a complementary (and not sole) tool to support reading comprehension in all subjects.
Keywords: Computer Science Applications; Human-Computer Interaction; Education; Mathematics (miscellaneous)

The presence of students identified as having special needs as a moderating effect on their classmates’ reading comprehension scores in relation to other major class composition effects - Krammer, Mathias; Seifert, Susanne; Gasteiger-Klicpera, Barbara (Educational Studies)
Keywords: Education

Comparing digital to print assessment of receptive vocabulary with GraWo‐KiGa in Austrian kindergarten - Paleczek, Lisa; Seifert, Susanne; Schöfl, Martin (British Journal of Educational Technology)
Keywords: Education

Teaching and learning in a multilingual Europe: findings from a cross-European study - Dockrell, J. E.; Papadopoulos, T. C.; Mifsud, C. L.; Bourke, L.; Vilageliu, O.; Bešić, E.; Seifert, Susanne; Gasteiger-Klicpera, B.; Ralli, A.; Dimakos, I.; Karpava, S.; Martins, M.; et al. (European Journal of Psychology of Education)
Abstract School classrooms within the EU are multilingual learning environments. The diversity of pupils in classrooms raises significant challenges for teachers, but to date, there are no data from large-scale surveys that compare views within and across European countries. A bespoke questionnaire was designed to examine views of current classroom learning environments with respect to the multilingualism. The questionnaire was piloted and subsequently completed by 2792 teachers across different European countries. Eleven countries provided sufficient data for analyses. Results from structural equation modelling showed that teachers’ attitudes could be reliably measured across Europe with the use of carefully devised questionnaire, whose loading and factor structure remained invariant across countries. Teachers’ views about multilingualism were most challenged by the numbers of children in their classes, not the percentage of multilingual pupils in the class. Countries differed in how they perceived multilingualism, with their differences leading to distinctive country clusters. Gender and education level (elementary vs. secondary) differences were also observed irrespective of country. These findings enhance our understanding of the role that the characteristics of teachers and their classrooms play in a multilingual setting across diverse European settings. The practical relevance of the results and new opportunities for teacher training are discussed.
Keywords: Developmental and Educational Psychology; Education

Moderne Heldin im antiken Gewand? Anne Webers „Annette, ein Heldinnenepos“ - Süwolto, Leonie

Zeit als Widerfahrnis. Ästhetik und Figuration passiv erfahrener Temporalität - Öhlschläger, Claudia; Roselli, Antonio (ZfdPh)

Haus-Komödien: Renaissancen des Lustspielsbei Ludovico Ariosto und William Shakespeare ("I Suppositi", "The Taming of the Shrew") - Steigerwald, Jörn (Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas.)

»Stilistik« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

»Abweichung« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

»abweichen« - Schuster, Britt-Marie (Text- und Diskurslinguistik)

Building, emptying out, or dreaming? Action structures and space in students’ metaphors of academic writing - Scharlau, Ingrid; Karsten, A.; Rohlfing, Katharina J. (Journal of Writing Research)
Keywords: Literature and Literary Theory; Linguistics and Language; Language and Linguistics; Education

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils Frederik; Crawshaw, Camilla E.; Rohlfing, Katharina J. (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.

Do Shy Children Keep more Distance from a Social Robot? Exploring Shy Children’s Proxemics with a Social Robot or a Human - Tolksdorf, Nils Frederik; Viertel, Fanziska E.; Crawshaw, Camilla E.; Rohlfing, Katharina J. (Interaction Design and Children)

In Krisen erzählen – von Krisen erzählen. Sprachliche, literarische und mediale Dimensionen.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Mehrdeutigkeiten
Keywords: General Earth and Planetary Sciences; General Environmental Science

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils F.; Crawshaw, Camilla E.; Rohlfing, Katharina (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.
Keywords: Education

Progressive Reduction of Iconic Gestures Contributes to School-Aged Children’s Increased Word Production - Rohlfing, Katharina; Mertens, Ulrich (Frontiers in Psychology)

Do Shy Preschoolers Interact Differently When Learning Language With a Social Robot? An Analysis of Interactional Behavior and Word Learning - Tolksdorf, Nils Frederik; Viertel, Franziska E.; Rohlfing, Katharina J. (Frontiers in Robotics and AI)
Temperamental traits can decisively influence how children enter into social interaction with their environment. Yet, in the field of child–robot interaction, little is known about how individual differences such as shyness impact on how children interact with social robots in educational settings. The present study systematically assessed the temperament of 28 preschool children aged 4–5 years in order to investigate the role of shyness within a dyadic child–robot interaction. Over the course of four consecutive sessions, we observed how shy compared to nonshy children interacted with a social robot during a word-learning educational setting and how shyness influenced children’s learning outcomes. Overall, results suggested that shy children not only interacted differently with a robot compared to nonshy children, but also changed their behavior over the course of the sessions. Critically, shy children interacted less expressively with the robot in general. With regard to children’s language learning outcomes, shy children scored lower on an initial posttest, but were able to close this gap on a later test, resulting in all children retrieving the learned words on a similar level. When intertest learning gain was considered, regression analyses even confirmed a positive predictive role of shyness on language learning gains. Findings are discussed with regard to the role of shyness in educational settings with social robots and the implications for future interaction design.

Komplexe Wörter richtig schreiben. Wortanalyse als Rechtschreibstrategie. - Lang, Susanne; Topalović, Elvira (In: Praxis Deutschunterricht)

Rechtschreibstrategien und Sprachstrukturen. - Noack, Christina; Topalović, Elvira (In: Praxis Deutschunterricht)

Ethical Considerations of Applying Robots in Kindergarten Settings: Towards an Approach from a Macroperspective - Tolksdorf, Nils Frederik; Siebert, Scarlet; Zorn, Isabel; Horwath, Ilona; Rohlfing, Katharina J. (International Journal of Social Robotics)
Abstract In child–robot interaction (cHRI) research, many studies pursue the goal to develop interactive systems that can be applied in everyday settings. For early education, increasingly, the setting of a kindergarten is targeted. However, when cHRI and research are brought into a kindergarten, a range of ethical and related procedural aspects have to be considered and dealt with. While ethical models elaborated within other human–robot interaction settings, e.g., assisted living contexts, can provide some important indicators for relevant issues, we argue that it is important to start developing a systematic approach to identify and tackle those ethical issues which rise with cHRI in kindergarten settings on a more global level and address the impact of the technology from a macroperspective beyond the effects on the individual. Based on our experience in conducting studies with children in general and pedagogical considerations on the role of the institution of kindergarten in specific, in this paper, we enfold some relevant aspects that have barely been addressed in an explicit way in current cHRI research. Four areas are analyzed and key ethical issues are identified in each area: (1) the institutional setting of a kindergarten, (2) children as a vulnerable group, (3) the caregivers’ role, and (4) pedagogical concepts. With our considerations, we aim at (i) broadening the methodology of the current studies within the area of cHRI, (ii) revalidate it based on our comprehensive empirical experience with research in kindergarten settings, both laboratory and real-world contexts, and (iii) provide a framework for the development of a more systematic approach to address the ethical issues in cHRI research within kindergarten settings.

Plattdeutsch im Kreis Höxter. "Der Dialektatlas Mittleres Westdeutschland (DMW)" und die Frage "Wie klingt Plattdeutsch im Kreis Höxter?" - Wallmeier, Nadine (Kreis Höxter Jahrbuch)

Das paderbörnische Platt. Niederdeutsch im Gebiet der Kreise Paderborn und Höxter - Tophinke, Doris; Wallmeier, Nadine; Merten, Marie-Luis

Ein kaiserlicher Wüterich und zwei antagonistische Simons. Der „Nero furens“ als Beispiel aus dem Paderborner Jesuitendramenkorpus - Elit, Stefan (NlatJb 23)

Diagnosen (h)erstellen – Sprachwissenschaftliche Zugänge - Felder, Ekkehard; Schuster, Britt-Marie; Spranz-Fogasy, Thomas (Linguistik und Medizin)
Keywords: Fachkommunikation

Widersprechen als diskursive Praktik. Illustriert an der Widerstandskommunikation gegen den Nationalsozialismus (1933–1945) - Schuster, Britt-Marie (Protest, Protestieren, Protestkommunikation)
Keywords: Kommunikationsgeschichte

Bedeutungsvarianz und sozialer Stil - Schuster, Britt-Marie; Wilk, Nicole M. (Sprache des Sterbens – Sprache des Todes. Linguistische und interdisziplinäre Perspektivierungen eines zentralen Aspekts menschlichen Daseins)
Keywords: Textsemantik

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

"Durch die Synästhesie wird deutlich, dass...". Die Wirkung sprachlicher MIttel in Gedichten erklären - Scholle, Oliver; Risse, Sylvia (Praxis Deutsch)

Building, emptying out, or dreaming? Action structures and space in undergraduates’ metaphors of academic writing - Scharlau, Ingrid; Karsten, Andrea; Rohlfing, Katharina (Journal of Writing Research)
The aim of the present study is to bring new momentum into research on students’ understanding of academic writing. Drawing on the idea that metaphors give insight into implicit conceptions of abstract entities and processes, we developed a detailed and differentiated set of conceptual metaphors that can be used to study student ideas about writing in research, teaching, and interventions. A large sample of undergraduates produced their everyday understanding of writing in short texts beginning with a self-generated metaphor. Based on theories from cognitive linguistics, the conceptual metaphors in their texts were analyzed in terms of their action quality (transitivity) and spatiality (spatial primitives). The undergraduates’ conceptualizations were very heterogeneous. Most metaphors depart strongly from scientific approaches to academic writing within cognitive psychology and sociocultural theory. Roughly half of the metaphors could be collated to one of four metaphor systems. Depending on the desired degree of abstraction or concreteness, conceptual metaphors or metaphor systems can be employed in further studies to illuminate thinking about writing.
Keywords: metaphor analysis; academic writing; transitivity; spatial primitives

Kinder- und Jugendliteratur intermedial. Unterrichtsanregungen und -materialien zum literarischen Lernen im Medienverbund anhand von Emil und die Detektive (Gym/Ge) und Jakob der Lügner (BK); erstellt von Masterstudierenden der Universität Paderborn

Obsolete Männlichkeit. Serienästhetisches Lernen an geschlechtskodierten Körperbildern in der Romanadaption BABYLON BERLIN - Kißling, Magdalena; Neumeier, Maya Marie (Studia Germanica Posnaniensia)

'Abgrund Mensch': Judith Kuckarts Um- und Weiterschriften der 'westfälischen Heimatdichterin' Annette von Droste-Hülshoff - Morrien, Rita (Arbeitsbuch Judith Kuckart. Erzählen - Theater - Tanz)

"Ich gehe durch andere Räume. Ich gehe durch eure Träume." - (Nicht-)Orte der Liebe in Judith Kuckarts "Kein Sturm, nur Wetter" - Morrien, Rita (Arbeitsbuch Judith Kuckart)

„Zunge: Sprache“ Literarische Mehrsprachigkeit im Deutschunterricht am Beispiel der Erzählung „Mutterzunge“ von Emine Sevgi Özdamar - Büttner, Denise; Roll , Heike (Vermitteln - verbinden - verstehen. 46. Jahrestagung des Fachverbandes Deutsch als Fremd- und Zweitsprache an der Technischen Universität Chemnitz)

Forcierte Form

Zeitschrift für deutsche Philologie (Herausgebertätigkeit von Norbert Otto Eke ab Bd. 123, 2004)

"Solange dieser Mann gut Deutsch sprechen kann, ist auch kein Problem...": Evaluative Reaktionen auf einen L2-Akzent aus Sicht von Sprecher*innen - Müller, Mareike; Settinieri, Julia (Fremdsprachen Lehren und Lernen)
This article investigates learners’ accounts of and reactions to interlocutors’ evaluations of their L2 pronunciation. Previous studies demonstrate both the pervasiveness of social evaluation processes in native and non-native speaker interactions and the impact of learners’ beliefs about pronunciation on their learning and communicative behavior. Adding to these strands of research, this project sheds light on how learners perceive evaluative reactions to their accents by native speakers and the relationship between such evaluations and learners’ reported evaluative, emotional and behavioral responses. The study draws on 8 international students at a German university. The data were collected in semi-structured interviews and analyzed within the framework of qualitative content analysis. The results give insight into conditions and strategies that may support learners in establishing constructive interpretations of the effects of their accents on their social acceptance.

»ich wusste doch irgendwas war zu einfach«. Gesprächsanalytische Betrachtungen von Proberunden zum Lernen von Gesellschaftsspielen - Menke, Peter (Kommunikationsdynamiken zwischen Mündlichkeit und Schriftlichkeit. Festschrift für Barbara Job zum 60. Geburtstag)

Vormärz-Handbuch

„Romantik“ und „Vormärz“. Ein Streitfall - Eke, Norbert Otto (Georg Büchner und die Romantik)

Ethische Erinnerungskultur. Peter Weiss‘ Memorial des ‚ganzen‘ Widerstands - Eke, Norbert Otto (Peter Weiss erinnernd – Ansichten und Einsichten)

Vormärz – Prolegomenon einer Epochendarstellung - Eke, Norbert Otto (Vormärz-Handbuch)

Vormärz und Klassik - Eke, Norbert Otto (Vormärz-Handbuch)

Vormärz und Aufklärung - Eke, Norbert Otto (Vormärz-Handbuch)

Exil - Eke, Norbert Otto (Vormärz-Handbuch)

Habitueller Antiklassizismus. Christian Dietrich Grabbe und die Kritik an Klassik und Romantik im Vormärz - Eke, Norbert Otto (Zwischen Emanzipation und Sozialdisziplinierung: Pädagogik im Vormärz)

Nachruf: Hartmut Steinecke zum Gedenken - Eke, Norbert Otto (Zeitschrift für deutsche Philologie)

Der ‚Eigene Kalender‘ des Erinnerns: Die Wahrheit der erfundenen Erinnerung in Herta Müllers Romanen, Erzählungen und Essays - Eke, Norbert Otto (German Life and Letters (Special Issue: Herta Müller and the Currents of European History))

Herta Müller. Text + Kritik 155/2020. 2. Auflage: Neufassung. Hg. von Norbert Otto Eke und Christof Hamann. (edition text + kritik)

Kurzreferat über: Lungershausen, Gerrit: Weltkrieg mit Worten. Kriegsprosa im Dritten Reich 1933 bis 1940. Wiesbaden: J.B. Metzler 2017 - Willeke, Stephanie (Germanistik. Internationales Referatenorgan mit bibliographischen Hinweisen 61 (H. 1-2))

Der unzuverlässige Zeuge – Störungen im Erinnerungsdiskurs ‚Shoah‘ - Willeke, Stephanie (Trauma-Erfahrungen und Störungen des ‚Selbst‘. Mediale und literarische Konfigurationen lebensweltlicher Krisen)

Ludwig Tieck - Willeke, Stephanie (Vormärz-Handbuch)

Der literarische Weblog als digitales Gedächtnismedium – Erinnerungen als Schreib- und Rezeptionspraktiken in Benjamin Steins Turmsegler - Willeke, Stephanie (Inszenierung des Buchs im Internet (Medium Buch. Wolfenbütteler interdisziplinäre Forschungen))

Kompetenzzuwachs und veränderte Unterrichtspraxis. Erste Ergebnisse aus der Evaluation eines DaZ-Weiterbildungsstudiums für Lehrkräfte an beruflichen Schulen - Böttger, Lydia; Groh, Olga; Otto, Lisa; Fischer, Nele; Hammer, Svenja; Jung, Ulla; Niederhaus, Constanze (Berufliche Integration durch Sprache. Reihe: Berichte zur beruflichen Bildung)

Integriertes Fach- und Sprachlernen in der beruflichen Bildung mittels Schreibwerkstatt für neu zugewanderte Lernende - Dohmann, Olga; Drumm, Sandra; Niederhaus, Constanze (Berufliche Integration durch Sprache)

Weiterbildendes Studium „Deutsch als Zweitsprache und Mehrsprachigkeit“ an der Universität Paderborn. Ausgestaltung und Evaluation einer Professionalisierungsmaßnahme im Bereich Inklusion - Berkel-Otto, Lisa; Böttger, Lydia; Fischer, Nele; Vasylyeva, Tetyana; Hammer, Svenja; Niederhaus, Constanze (Journal für Psychologie, 27(2))

Gedenkschrift für Jörg Riecke - Ptashnyk, Stefaniya (Wörter – Zeichen der Veränderung (Studia Linguistica Germanica))

Language Variation in multilingual historical settings - Ptashnyk, Stefaniya (“VARIATIONist Linguistics meets CONTACT Linguistics”)

Einleitung - Ptashnyk, Stefaniya; Bopp, Dominika; Roth, Kerstin; Theobald, Tina (Wörter – Zeichen der Veränderung. Gedenkschrift für Jörg Riecke)

Animalische Epistemologie: Tierwahrheiten bei Franz Kafka am Beispiel von "Ein Bericht für eine Akademie" - Tönsing, Johanna

Strategieorientierte Therapie mit dem Wortschatzsammler - (nicht nur) für Kinder mit Wortfindungsstörungen - Ulrich, Tanja (Nur ein Wort? Diagnostik und Therapie von Wortabrufstörungen bei Kindern und Erwachsenen. Spektrum Patholinguistik)

Gedankenhöhlen. Beteiligungschancen an literarischen Gesprächen stiften - Kruse, Iris (Die Grundschulzeitschrift)

Intermediale Lektüre - Kruse, Iris (Handbuch Kinder- und Jugendliteratur)

Literatursprache im Medienvergleich erfahren. Literaturbezogene sprachliche Handlungserweiterungen in Lehr-Lernarrangements zu kinderliterarischen Medienverbünden - Kruse, Iris (Sprache als Herausforderung - Literatur als Ziel. Kinder- und jugendliterarische Texte und Medien als Ressource für sprachsensibles Lernen)

Das starke Kind. Resilienz als Motiv in der Kinderliteratur - Kruse, Iris; Terhorst , Sarah (Kinder- und Jugendmedien im inklusiven Blick. Analytische und didaktische Perspektiven)

Abenteuerlich (und) intermedial. Zur Medienverbunddidaktik und zu Lernchancen des seriell verfilmten Mittelalterromans "Der kleine Ritter Trenk" von Kirsten Boie - Kruse, Iris (Literarisches Lernen mit Medienverbünden für Kinder und Jugendliche. Abenteuer/âventiure als narrativer Zugang in Theorie und Praxis)

Vom Selbst- zum Gruppengespräch. Gedankenhöhlen zur Vorbereitung auf den Austausch über Literatur - Kruse, Iris (Praxis Deutsch (Gespräche über Literatur))

Topographische Grenzgänge in die Unterwelt: Sterben als Suche in David Grossmanns Aus der Zeit fallen - Harmening, Anda-Lisa Martha Josephine Anna (Störungen des 'Selbst' – Trauma-Erfahrungen und Möglichkeiten ihrer künstlerischen Konfiguration)

(Text)Körper und Macht – Politische Interventionen in Juli Zehs Corpus Delicti - Harmening, Anda-Lisa Martha Josephine Anna (Politische Interventionen und Spielräume in der Gegenwartsliteratur von Autorinnen)

Intersections of Gender and Myth in canadian culture and Media

Literatur im Studium Deutsch als Fremdsprache und in der internationalen Germanistik: Sprachbildung und Förderung interkultureller Kompetenzen durch literarische Texte - Zierau, Cornelia (Germanistik im Kontext des LMD-Systems. Didaktische und curriculare Herausforderung einer regionalen Hochschulpolitik für das Deutsch-Studium in Westafrika)

Sprachsensibler Literaturunterricht mit „Tschick“. Sprachliches und literar-ästhetisches Lernen in einem integrativen Deutschunterricht? - Zierau, Cornelia; Kofer, Martina (Sprache als Herausforderung – Literatur als Ziel. Kinder- und jugendliterarische Texte und Medien als Ressource für sprachsensibles Lernen Teil 2)

Übergänge gestalten – eine Herausforderung - Zierau, Cornelia; Jung, Ulla (DaZ Sekundarstufe. Konzepte und Materialien: Übergänge gestalten – neu Zugewanderte unterrichten, Heft 1/2020)

„Ich verkaufte ihm meinen Fastentag für 25 Kuruş und mit diesem Geld ging ich ins Kino.“ Mehrsprachigkeit und Übersetzung ,türkischer’ Kultur in Emine Sevgi Özdamars Roman „Das Leben ist eine Karawanserei“ - Zierau, Cornelia (Peter Weiss Jahrbuch)

wirmüssentanzen. Methodische Überlegungen zur linguistischen Analyse von (Selbst-) Inszenierungen von Amateursportlern in den sozialen Medien am Beispiel Racing Aloha auf Instagram - Kurpiers, Anna-Katharina (Kommunikationsdynamiken zwischen Mündlichkeit und Schriftlichkeit. Festschrift für Barbara Job zum 60. Geburtstag)

„So dacht ich. Demnächst mehr.“ Modelle narrativer Ethik und narrativer Identität in Hölderlins ‚Hyperion’ und Schillers ‚Demetrius’ - van Laak, Lothar (Erzähltes Selbst. Narrative Ethik aus theologischer und literaturwissenschaftlicher Sicht. (Theologie - Kultur - Hermeneutik, Bd. 27))

Barock im Norden. Kommunikationspraxis und Kulturtransfer - van Laak, Lothar; Ehland, Christoph; Münzmay, Andreas; Schmitz, Sabine; Süßmann, Johannes (Peter Paul Rubens und der Barock im Norden. Katalog zur Ausstellung im Erzbischöflichen Diözesanmuseum Paderborn)

„eine andere Ähnlichkeit“ – Musik und Literatur bei Moses Mendelssohn und Gotthold Ephraim Lessing - van Laak, Lothar (Dialog der Künste. Literatur und Musik)

Erzählen und Ehtik in Peter Weiss’ ‚Rekonvaleszenz’. In: Erzähltes Selbst. Narrative Ethik aus theologischer und literaturwissenschaftlicher Sicht - van Laak, Lothar ((Theologie - Kultur - Hermeneutik, Bd. 27).)

Typen der deutschsprachigen Versepik 1745/1848 - Elit, Stefan (Forcierte Form. Deutschsprachige Versepik des 20. und 21. Jahrhunderts im europäischen Kontext (Abhandlungen zur Literaturwissenschaft))

Versepik - Elit, Stefan (Vormärz-Handbuch)

Ferdinand von Fürstenberg - Elit, Stefan (Frühe Neuzeit in Deutschland. 1620-1720. Literaturwissenschaftliches Verfasserlexikon (VL17), Bd. III)

Hartmann von Aue 1230–1517. Kulturgeschichtliche Perspektiven der handschriftlichen Überlieferung

Figuren des Dritten im höfischen Roman, Beiträge zur mediävistischen Erzählforschung 2020, Themenheft 4

„Zeit, Raum und Subjektivität bei Hartmann von Aue und Burkhard von Hohenfels“ - Egidi, Margreth (Raum und Zeit im Minnesang. Ansätze – Spielarten – Funktionen (Studien zur historischen Poetik 29))